Relação professor aluno: Uma relação transcendente a sala de aula refletida na trajetória do aluno - SOUZA, Izaldo Sene de (2023)
The theme Teacher-student relationship: a transcendent relationship in the classroom reflected in the student's trajectory, presented in this work as a memorial, aims to show my personal, student, teaching and academic life trajectory, also to bring to light the importance of the role that teachers exercise in the life and future decisions of their students, which through reports of my memories I offer a reflection on where we as education professionals have in relation to our students, because on numerous occasions we assume the role not only role of teacher in each one's lives and that this relationship transcends the classroom floor, going beyond the walls and patios of the school. This work is based on theorists such as Imbernón (2010), Rios (2010), Mantoan (2015), Tardiff (2012), Freire (1987) and (1996), which deal with themes proposed in this work. To build this work, I will use autobiographical, reflective and bibliographical descriptive research, where I will present remarkable facts from my childhood, how I started my student life, the progress and challenges faced during the school and personal journey, the beginning of my professional career, my entry at one of the most renowned and desired universities in the country, the Federal University of Pará - UFPA, the importance of the basic education teacher training program - PARFOR and finally expose the result of this research. whenever possible, trying to intertwine the context of the research with the theme addressed, using a qualitative approach as a channel, proposing to bring to light the reflection once said